IMPLEMENTASI FILSAFAT ILMU PERTAHANAN DALAM KEBIJAKAN PERTAHANAN DAN PENYELENGGARAAN PERTAHANAN NEGARA - Pratama, Robbyanandri; Khairunnisa, Nila Aulia (PPM Sdirjianbang Akademi Militer, 2024)
The implementation of the Philosophy of Defense Science in defense policy and national defense administration, aiming to enhance the nation’s defense capabilities. Through a philosophical approach encompassing ontology, epistemology, and axiology, the article explains the importance of applying philosophy to understand and develop Defense Science. The method used is a literature review, which examines the role of Defense Science in addressing both military and non-military threats, as well as its application in national defense policies such as the Total People’s Defense System (Sishankamrata). The key findings show that the Philosophy of Defense Science contributes to increasing awareness of national defense and citizen participation. In conclusion, this philosophy plays a crucial role in shaping holistic and participatory defense policies, involving all elements of the nation.